Endoscopic closure of experimental iatrogenic gastric fundus perforation using over‐the‐scope clips in a surviving canine model. Issue 9 (22nd August 2013) - Zhang, Xiu Li; Sun, Gang; Tang, Ping; Zhang, Ru Gang; Yang, Yun Sheng
Abstract: Background and Aim: To evaluate the effectiveness and outcomes of endoscopic closure of a gastric fundus perforation using over‐the‐scope clips (OTSCs) system in a surviving canine model. Methods: Gastric fundus perforations (20‐mm diameter) were created by an endoscopic needle‐knife in six dogs. The perforations then were closed by the OTSC system. Gastroscopy was performed to evaluate the postoperative perforation healing every week. The animals were sacrificed 4 weeks later to examine the possible intraperitoneal complications, and the healing of the perforation was examined histopathologically. Results: The gastric fundus perforations could primarily be closed using one OTSC in each experimental dog, and the mean time of the procedure was 17.3 ± 7.6 min (9–26 min). All animals survived without postoperative complications. The OTSC retention was observed in one dog at the end of 4 weeks, and the apparent foreign‐body reaction was examined pathologically. Conclusions: Our surviving animal study demonstrated that the OTSC clip system could reliably close gastric fundus perforations without complications.